An Ongoing Concern of Diabetic Management with SGLT2i - Its Potential Medico-Legal Implication - Wong, Wu Shun Felix; Yeung, Vincent Tok Tai (International Journal of Innovative Research in Medical Science, 2024)
Diabetic Ketoacidosis (DKA) is a life-threatening diabetic emergency. There is now an emerging risk of DKA because of a potential adverse effect of the new diabetic medication - Sodium Glucose Transporter 2 inhibitor (SGLT2i) that can lead to diabetic ketoacidosis. This paper shares our experience of unexpected events in two diabetic patients taking SGLT2i, resulting in urgent hospitalization in one case and medical litigation in the other. It also brings to the doctors' attention that ketone breath sensors are now available to diagnose DKA quickly and accurately. They can offer a non-invasive approach to detecting and monitoring DKA in diabetic patients; hopefully, it could have averted similar events and prevented medical litigation in the future.